2014
DOI: 10.1051/0004-6361/201323143
|View full text |Cite
|
Sign up to set email alerts
|

Energy and helicity budgets of solar quiet regions

Abstract: Aims. We investigate the free magnetic energy and relative magnetic helicity budgets of solar quiet regions. Methods. Using a novel nonlinear force-free method that requires single solar vector magnetograms we calculated the instantaneous free magnetic energy and relative magnetic helicity budgets in 55 quiet-Sun vector magnetograms. Results. As in a previous work on active regions, we constructed here for the first time the (free) energy-(relative) helicity diagram of quiet-Sun regions. We find that quiet-Sun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 43 publications
(86 reference statements)
7
22
0
Order By: Relevance
“…5.2.5), NLFF models have recently been applied to investigate the magnetic energy and helicity budget in the QS. Tziotziou et al (2014) performed a statistical study with a large number of quiet-Sun vector magnetograms from Hinode/SOT-SP. They found that the QS has no dominant sense of helicity (in contrast to ARs) and that both the free magnetic energy and the relative magnetic helicity are correlated with the area occupied with network elements.…”
Section: Magnetic Energy and Helicity Budgetmentioning
confidence: 99%
“…5.2.5), NLFF models have recently been applied to investigate the magnetic energy and helicity budget in the QS. Tziotziou et al (2014) performed a statistical study with a large number of quiet-Sun vector magnetograms from Hinode/SOT-SP. They found that the QS has no dominant sense of helicity (in contrast to ARs) and that both the free magnetic energy and the relative magnetic helicity are correlated with the area occupied with network elements.…”
Section: Magnetic Energy and Helicity Budgetmentioning
confidence: 99%
“…Stochastic photospheric motions provide the asymmetric processes and helicity injections necessary to generate non-potential magnetic fields (Woodard & Chae 1999;Chesny et al 2013;Uritsky et al 2013;Wiegelmann et al 2013). Tziotziou et al (2014) subsequently determined that the free magnetic energy and helicity budgets of the QS network are sufficient to sustain finescale network structuring. The presented observations of flaring non-potential fields alone are strong evidence that there also exists sufficient free magnetic energy in the QS-like network to initiate a process or processes akin to sigmoid formation.…”
Section: General Commentsmentioning
confidence: 99%
“…In quiet-Sun regions, including the magnetic network, there is substantial lack of studies concerning accumulation and expulsion of helicity. Zhao et al (2009) have investigated current helicity budgets in network bright points, while studies by Welsch & Longcope (2003), Georgoulis et al (2009), andTziotziou et al (2014a) refer to total helicity budget derivations in the quiet Sun. However, observations suggest the presence of twist and torsional motions in fine structures, Article published by EDP Sciences A61, page 1 of 8 such as explosive events and spicules (Jess et al 2009;Curdt & Tian 2011;De Pontieu et al 2012) and the whole quiet Sun (De Pontieu et al 2014), which could infer the expulsion or transfer of helicity from small-scale structures to larger scales in the quiet solar atmosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The method was mostly applied in solar ARs Tziotziou et al 2012Tziotziou et al , 2013Tziotziou et al , 2014b. However, it was also successfully used by Tziotziou et al (2014a) in quiet-Sun regions for deriving the instantaneous budgets of free magnetic energy and relative magnetic helicity, respective budgets within a solar cycle and monotonic relations between the two quantities and between both quantities and the network area.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation